Draft animal power and agricultural development in hot zones: an annotated bibliography - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Draft animal power and agricultural development in hot zones: an annotated bibliography